Development of an Elongated Ellipsoid Heat Source Model to Reduce Computation Time for Directed Energy Deposition Process - Nain, Vaibhav; Engel, Thierry; Carin, Muriel; Boisselier, Didier; Seguy, Lucas (Frontiers in Materials, 2021)
Directed Energy Deposition (DED) Additive Manufacturing process for metallic parts are becoming increasingly popular and widely accepted due to their potential of fabricating parts of large dimensions. The complex thermal cycles obtained due to the process physics results in accumulation of residual stress and distortion. However, to accurately model metal deposition heat transfer for large part dimension, numerical model leads to impractical computation time. In this work, a 3D transient finite element model with Quiet/Active element activation is developed for modeling metal deposition heat transfer analysis of DED process. To accurately model moving heat source, Goldak’s double ellipsoid model is implemented with small enough simulation time increment such that laser moves a distance of its radius over the course of each increment. Considering thin build-wall of Stainless Steel 316L fabricated with different process parameters, numerical results obtained with COMSOL 5.6 Multi-Physics software are successfully validated with experiment temperature data recorded at the substrate during the fabrication of 20 layers. To reduce the computation time by reducing the total simulation time increments, elongated ellipsoid heat input model that averages the heat source over its entire path is implemented. It has been found that by taking such large time increments, numerical model gives inaccurate results. Therefore, the track is divided into several linear sub-tracks, each of which is applied in one simulation increment. In this work, an investigation is done to find out the correct simulation time increment or sub-track size that leads to reduction in computation time (5-10 times) but still yields sufficiently accurate results ( below 10% of relative error on temperature). Finally, a Correction factor is introduced that further reduces computation error of elongated heat source. A new analytical relation is also established in finding out the correct time increment and correction factor value to drastically reduce the computation time yielding accurate results.